2017
DOI: 10.12775/eq.2017.029
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability of Gladiolus imbricatus L. populations in different plant communities near Kraków

Abstract: Abstract. The investigations, aimed to assess the abundance, stage structure and distribution of shoots, as well as the chosen traits of generative shoots (number of leaves and length of the longest one, height of shoot, length of inflorescence and the dorsal tepal of the lowermost flower, number of seed capsules) of Gladiolus imbricatus L. were conducted in the years 2015-2017. The observations were carried out from Kraków-Pychowice to Tyniec in abandoned moor-grass meadow (Patch I), shrub willows (Patch II),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…A similar phenomenon was also presented by other species occurring in meadows subjected to secondary succession, e.g., Iris sibirica [54,55] and Trollius europaeus [56]. Te greater height of shoot and length of inforescence of Gladiolus imbricatus in unmanaged meadow is consistent with the fndings of Kostrakiewicz-Gierałt [37] and might help enlarge the visibility of fowers and augment the chance for successful pollination from the order Hymenoptera, which are attracted particularly by blue, pink, purple, and mauve colours in the vicinity of tall plants [57][58][59]. Moreover, the results of the research of Chelariu and Draghia [35], showing a greater height of shoots and fower number in inforescence in natural habitat than in cultivated, seem to correspond with the results found in the present study considering the fact that the unmanaged meadow (UM) has a more natural character than the extensively used meadow (EM) [54].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A similar phenomenon was also presented by other species occurring in meadows subjected to secondary succession, e.g., Iris sibirica [54,55] and Trollius europaeus [56]. Te greater height of shoot and length of inforescence of Gladiolus imbricatus in unmanaged meadow is consistent with the fndings of Kostrakiewicz-Gierałt [37] and might help enlarge the visibility of fowers and augment the chance for successful pollination from the order Hymenoptera, which are attracted particularly by blue, pink, purple, and mauve colours in the vicinity of tall plants [57][58][59]. Moreover, the results of the research of Chelariu and Draghia [35], showing a greater height of shoots and fower number in inforescence in natural habitat than in cultivated, seem to correspond with the results found in the present study considering the fact that the unmanaged meadow (UM) has a more natural character than the extensively used meadow (EM) [54].…”
Section: Discussionsupporting
confidence: 84%
“…We found that the length of the longest leaf blade and the height of the shoot, as well as the length of inforescence, number of capsules in infructescence, and the length of the greatest capsule are greater in the unmanaged meadow. Te larger dimensions of leaves allow G. imbricatus to efectively compete with neighbouring plants for light interception [36][37][38]. A similar phenomenon was also presented by other species occurring in meadows subjected to secondary succession, e.g., Iris sibirica [54,55] and Trollius europaeus [56].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation